Bone Mineral Parameters in Peritoneal Dialysis Patients after Lowering Calcium Concentration in Dialysis Fluids: A Case Series in Patients Using Icodextrin - Lara C. Verschuur; Anouschka G. Liefting; Bastiaan van Dam; Erik L. Penne; Fenneke C. Frerichs (Case Reports in Nephrology and Dialysis, 2023)
In patients treated with peritoneal dialysis (PD), lowering the calcium level in PD fluids results in lower serum calcium levels and higher parathyroid hormone (PTH) levels. It is hypothesized that this effect is attenuated when patients are using icodextrin 7.5% for the once-daily long dwell (containing high calcium concentration). In this case series, we included 8 stable PD patients (mean age 68 ± 13 years, 7 male), all using icodextrin 7.5% (containing 1.75 mmol/L calcium) for the once-daily long dwell. The calcium content of the PD fluids for the remaining dwells was lowered from 1.75 mmol/L to 1.25 mmol/L. Bone mineral parameters and phosphate prescription at baseline, 6 weeks after this change, and after 6 months were compared. After lowering calcium concentration of the PD fluids – except for the icodextrin 7.5% – from 1.75 mmol/L to 1.25 mmol/L, calcium levels changed from 2.32 ± 0.11 to 2.29 ± 0.12 (p = NS); intact PTH (iPTH) from 39.6 ± 28.3 to 64.9 ± 34.5 pmol/L (p = 0.045); and alkaline phosphatase from 104.13 ± 48.75 to 101.38 ± 32.39 (p = NS). After 6 months, all bone mineral parameters were similar to baseline levels; however, slightly higher calcium-based phosphate binders were prescribed. Lowering calcium content from 1.75 mmol/L to 1.25 mmol/L in PD fluids in patients on icodextrin resulted in stable calcium values, a temporal increase in iPTH and a modest increase in calcium-based phosphate binder prescription. Using icodextrin for the long once-daily dwell appears to attenuate the effects on bone mineral parameters when lowering the calcium concentration of the short dwells.